On solving the system of linear partial differential equations in Dirichlet series - Kleiza, J. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Клейза. О решении системы линейных дифференциальных уравнений в частных производных рядами Дирихле J. Kleiza. Apie tiesinių diferencialinių lygčių su dalinėmis išvestinėmis sistemos sprendimą Dirichlė eilutėmis